Novel Auditory Displays in Highly Automated Vehicles: Sonification Improves Driver Situation Awareness, Perceived Workload, and Overall Experience. (September 2021) - Nadri, Chihab; Ko, Sangjin; Diggs, Colin; Winters, Michael; Sreehari, V. K.; Jeon, Myounghoon
Highly automated driving systems are expected to require the design of new user-vehicle interactions. Sonification can be used to provide contextualized alarms and cues that can increase situation awareness and user experience. In this study, we examined user perceptions of potential use cases for level 4 automated vehicles in online focus group interviews (N=12). Also, in a driving simulator study, we evaluated (1) visual-only display; (2) non-speech with visual display; and (3) speech with visual display with 20 young drivers. Results indicated participants' interest in the use cases and insight on desired functions in highly automated vehicles. Both audiovisual display conditions resulted in higher situation awareness for drivers than the visual-only condition. Some differences were found between the non-speech and speech conditions suggesting benefits of sonification for both driving and non-driving related auditory use cases. This study will provide guidance on sonification design for highly automated vehicles.